Mark Wolf at work in Dow Agricultural Research and Development Laboratory - Dow Chemical Company (1952)
General view of chemist Mark Wolf preparing a sample for analysis at the Dow Chemical Company's Agricultural Chemical Research and Development Laboratory facilities. Per an article in the August 1941 edition of the Dow Diamond, the department was responsible for studying the diseases of living plants, the effects of parasites, and the study and testing of insecticides, fungicides, and fumigants. As part of that research, chemists like Wolf were responsible for the small-scale compounding of insecticidal or fungicidal sprays or dusts, which were subsequently field-tested for uniform and effective distribution on foliage using standard equipment.
Keywords: Agricultural chemicals; Employees; Chemical industry; Scientific apparatus and instruments; Dow Chemical Company; Corporations; Agricultural chemistry; Laboratories; Wolf, Mark